2016
DOI: 10.1016/j.urology.2016.03.073
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Frailty Is Associated With Discharge to Skilled or Assisted Living Facilities After Urologic Procedures of Varying Complexity

Abstract: Purpose To evaluate the association between frailty and post-operative discharge destination after different types of commonly performed urologic procedures in older patients. Materials and Methods Using data from the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) from 2011–2013, we identified commonly performed inpatient urologic procedures among patients age 65 and older. We then assessed the effect of frailty, measured by the NSQIP Frailty Index (NSQIP-FI), on disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Frailty is a measure of physiologic vulnerability that manifests as increased susceptibility to adverse events such as falls, disability, loss of independence, and death . Among older individuals undergoing surgery, frailty has been linked to increased risk of postoperative complications and prolonged periods of recovery . Several validated measures that can be used to define frailty–a complex physiologic state.…”
Section: Introductionmentioning
confidence: 99%
“…Frailty is a measure of physiologic vulnerability that manifests as increased susceptibility to adverse events such as falls, disability, loss of independence, and death . Among older individuals undergoing surgery, frailty has been linked to increased risk of postoperative complications and prolonged periods of recovery . Several validated measures that can be used to define frailty–a complex physiologic state.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although we have previously shown that frailty is common among older individuals undergoing urologic surgery using the National Surgical Quality Improvement Program (NSQIP) Frailty Index, 8 such frailty assessment tools are not commonly utilized in practice. 4 In recognition of the need to improve surgical care among older individuals, the American College of Surgeons NSQIP and the American Geriatric Society have jointly recommended a frailty preoperative assessment for all patients 65 and older.…”
Section: Introductionmentioning
confidence: 99%
“…delirium and falls) that are related to non-home discharge. The evidence showed that a higher proportion of patients discharged to a location other-than-home experienced early mortality after RC compared to those discharged home [24,37,38]. Therefore, still bearing in mind the possible risk of selection bias related to the frail population, the increased rate of non-home discharge among frail patients undergoing RC could submit them to this additional risk of short-term mortality.…”
Section: Discussionmentioning
confidence: 99%